PERANCANGAN SISTEM KONTROL PID DENGAN APLIKASI SCILAB - Asmarita Sari; Fitri Jusmi (Applied Physics of Cokroaminoto Palopo, 2021)
PID control is a control that will react to the error that has been given by the sensor, so that it can provide an improvement value to the output value. The RLC circuit is an electrical circuit consisting of a resistor (R), an inductor (L) and a capacitor (C), which are arranged in series or parallel. The resistance produced by the resistor is referred to as resistance, the resistance produced by the inductor is usually called the inductive reactance symbolized by XL, while the resistance generated by the capacitor is called the capacitive reactance symbolized by XC. The method of solving an electric circuit can be solved by using the Laplace transform associated with using SCILAB software. SCILAB is open source software and can be run on Windows, Mac and Linux operating systems.